Collaborative epistemic discourse in classroom information-seeking tasks. Issue 1 (1st January 2017) - Knight, Simon; Mercer, Neil
Abstract : The authors discuss the relationship between information seeking and epistemic beliefs – beliefs about the source, structure, complexity and stability of knowledge – in the context of collaborative information-seeking discourses. They further suggest that both information seeking, and epistemic cognition research agendas, have suffered from a lack of attention to how information seeking as a collaborative activity is mediated by talk between partners – an area they seek to address in this article. A small-scale observational study using sociocultural discourse analysis was conducted with eight 11-year-old pupils who carried out search engine tasks in small groups. Qualitative and quantitative analysis were performed on their discussions using sociocultural discourse analytic techniques. Extracts of the dialogue are reported, informed by concordance analysis and quantitative coding of dialogue duration. The authors find that: (1) discourse which could be characterised as 'epistemic' is identifiable in student talk; (2) it is possible to identify talk which is more or less productive; and (3) epistemic talk is associated with positive learning outcomes.